2004
DOI: 10.1111/j.1399-3046.2004.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

BK viral infection in an Australian pediatric renal transplant population

Abstract: BK virus (BKV) is recognized as a significant cause of renal allograft dysfunction in adults, and there is growing awareness of its importance in the pediatric population. Eighteen pediatric renal transplant recipients and 18 age-matched controls were prospectively studied. Anti-BKV immunoglobulin G (IgG) and IgM titres were assayed in all subjects at entry to the study. Polymerase chain reaction (PCR) for BKV DNA was performed on urine and serum at entry, and prospectively tested again at 4, 8 and 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 16 publications
(28 reference statements)
2
40
2
1
Order By: Relevance
“…Besides these high frequencies of BKV infection signals, 5,21,[23][24][25][26] this study also confi rms the previous evidence of no clinical or histopathological characteristics associated with BKV infection. 2,24,26,27,28 In agreement with others, [26][27][28] there was no association with acute rejection or with its treatment. On the other hand, reinforcing the importance of an early diagnosis, no case of viremia among patients with current CAN highlights their probable severe renal damage hindering the viral replication.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Besides these high frequencies of BKV infection signals, 5,21,[23][24][25][26] this study also confi rms the previous evidence of no clinical or histopathological characteristics associated with BKV infection. 2,24,26,27,28 In agreement with others, [26][27][28] there was no association with acute rejection or with its treatment. On the other hand, reinforcing the importance of an early diagnosis, no case of viremia among patients with current CAN highlights their probable severe renal damage hindering the viral replication.…”
Section: Discussionsupporting
confidence: 73%
“…16,24,44,45 Finally, viremia is a late BKV-infection event, associated with graft dysfunction and works as a marker for BKN development. 28 It occurs 16 to 33 weeks previously to the establishment of BKN, 13 and invariably appears later than viruria. 36 Thus, an intense BKV-viruria predicts viremia, and probably BKN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reported to date are retrospective, or evaluate limited prospective sampling (13,(15)(16)(17). In our prospective study, the prevalence of BK viruria and viremia are 63% and 21%, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Reportes americanos de centros de trasplante renal confirman sostenido incremento del porcentaje de su prevalencia (5% a 10%) (1,2) . Emerge como una patolog铆a que puede ocasionar la p茅rdida del injerto en m谩s de la mitad de los casos (3)(4)(5)(6)(7)(8) .…”
Section: Introductionunclassified